2021
DOI: 10.1029/2021gl094168
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Feedback Accelerates the Formation of Typhoon Haiyan (2013): The Critical Role of Mid‐Level Circulation

Abstract: Tropical cyclones (TC) are among the most destructive geophysical phenomena on earth. It is well accepted that the wind-induced surface heat exchange feedback is the most responsible mechanism for the intensification and maintenance of TCs (e.g., Emanuel, 1989Emanuel, , 1995. However, the controlling mechanisms of TC genesis are still unsettled.The critical role of radiation feedback on TC genesis has been becoming more and more appreciated in recent years (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Different from the pathway of CRF which accelerates the TC development by accelerating the mid-level vortex (Ruppert et al, 2020;Yang et al, 2021), this study confirms the outflow blocking effect against the VWS. Physically, the CRF impact is closely associated with the distribution of cloud.…”
Section: Conclusion and Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Different from the pathway of CRF which accelerates the TC development by accelerating the mid-level vortex (Ruppert et al, 2020;Yang et al, 2021), this study confirms the outflow blocking effect against the VWS. Physically, the CRF impact is closely associated with the distribution of cloud.…”
Section: Conclusion and Discussionsupporting
confidence: 61%
“…Previous studies suggested that TC intensification is strongly related to their upper-level clouds and stratiform precipitation (Tao et al, 2017;Fischer et al, 2018;Zhang and Xu, 2021). Recent theoretical and modeling studies have suggested that the crucial role of cloud-radiation feedback (CRF) in TC genesis and development (Bu et al, 2014;Fovell et al, 2016;Wing et al, 2016;Ruppert et al, 2020;Smith et al, 2020;Yang and Tan, 2020;Yang et al, 2021). Ruppert et al (2020) suggested that the intensification of the secondary circulation forced by the radiative warming anomaly might transport more moisture and low-level angular momentum into the disturbance region, which directly promotes TC development.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, this ascent is also significant at the upper levels of the eyewall and drastically increases outward. This ascent structure results in the release of more latent heat on the outer side of the upper eyewall (Yang & Tan, 2020; Yang et al., 2021, Figure 4a), gradually tilting the eyewall heating in CNTL. Other conditions being equal, a tilted eyewall favors a relatively larger RMW (Figures 4c and 4e, Wang, 2008), ultimately reducing the inner‐core vorticity and inward vorticity flux.…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods will introduce a significant bias that may shift the background state. In this study, CRF is removed in the ARADI (average radiation) experiment by horizontally averaging radiative heating at every time step (Muller & Romps, 2018; Wing, 2022; Yang & Tan, 2020; Yang et al., 2021). The ARADI run restarts at hour 28 in CNTL, when the maximum tangential‐mean velocity at the 600 m height reaches 200.25emnormalm0.25ems1 $20\,\mathrm{m}\,{\mathrm{s}}^{-1}$.…”
Section: Simulation Designmentioning
confidence: 99%
See 1 more Smart Citation